Geothermal power plants : principles, applications and case studies - DiPippo, Ronald (Elsevier, 2005)
Geothermal Power Plants: Principles, Applications and Case Studies is the latest book from Ron DiPippo, Professor Emeritus, University of Massachusetts Dartmouth. It is a single resource on all aspects of the utilization of geothermal energy for electric power generation. Written in one voice by a respected authority in the field with twenty-five years of experience in geothermal research, teaching, and consulting, it is intended for those involved in any aspect of the geothermal industry. Grounded in fundamental scientific and engineering principles, its practical emphasis is enhanced by the.